Pengaruh Pelatihan Kerja dan Disiplin Kerja Terhadap Kinerja Petugas BPBD Kota Surabaya - Kartikawati, Liliek (Seminar Nasional Manajemen, 2025)
The Surabaya City Regional Disaster Management Agency (BPBD) faces significant challenges in handling complex emergency incidents, requiring well-trained human resources with a high level of work discipline. Without strong discipline, training becomes ineffective, potentially leading to delayed responses, poor decision-making, or team conflicts that hinder disaster management efforts. This study aims to analyze the influence of job training and work discipline on the performance of BPBD officers in emergency services. Employing a quantitative approach with an associative method, the research collected primary data through questionnaires and analyzed the results using SPSS 25. The findings indicate that job training contributes to improving officers' skills, work quality, and discipline, while work discipline enhances compliance with procedures and preparedness in emergency situations. Both factors significantly impact the professionalism and responsiveness of officers in managing emergencies. Future research is recommended to be more precise in defining the population and sample, as well as to use more valid instruments. BPBD Surabaya is encouraged to tighten supervision of work discipline, improve the quality of simulation-based training, and foster a vi professional and accountable work culture to enhance the effectiveness of emergency services.